A Multi-attribute decision analysis that justifies the conversion of the irrigation canals to multipurpose canals - Buendia, Roger Victor E.
The primary purpose of this paper is to study the inclusion of hydropower in irrigation canals using the Multi-attribute Decision Analysis(MDA) method.The intention is to develop an evaluation tool that provides critical information and assist decision makers in the government,especially the National Irrigation Administration (NIA),in realizing their mandate to construct multiple-purpose water resources projects designed primarily for irrigation,and secondarily for water supply and sanitation,flood control,and energy access,e.g.,hydro power development,to achieve security and self-sufficiency in food staples with a vision of farmers enjoying a decent and rising standards of living.But before a decision is made to integrate hydro power in the irrigation canal systems,other energy technologies that are potentially viable and better solutions to address the problem of energy access in the agricultural areas in a sustainable manner are investigated.The MDA method is a tool that government decision makers can use to aid their decision making on complex problems.The MDA model establishes quantitative representations of qualitative judgements,which are preferences based on subjective attributes such as,in the case of this study,cost to consumers,energy generation,climate change mitigation,grid impact,scalability,and socio-political acceptability.The coverage of the analysis is limited to farmland areas that have access to irrigation canals.Solar PV and diesel generator technologies are included in the study as alternative power resources to hydro.Incorporated in this paper are literature reviews and research works on the status of the hydro power technology,which offer the reason to believe that new technological developments demonstrate functional benefits of low head hydro power in irrigation canals.The MDA results supported the move of integrating hydro power in the irrigation canals in lieu of the other alternative energy resources.Amongst the attributes,the socio-political acceptability can widely change depending on the different and many stakeholders in the electricity market.With this,NIA needs to initiate a collaboration between pertinent government agencies such as the Department of Agriculture,Department of energy, National Electrification Administration,National Water Resources Board,Department of Public Works and Highways,and Department of Science and Technology,as well as the farmers,as recipients of the benefits,to form an integrated policy that will ensure the successful implementation of a program that converts the use of agricultural water systems from irrigation canals to multipurpose canals.